Description of the female and natural history of Clothoda tocantinensis Krolow & Valadares, 2016 (Embioptera: Clothodidae) - Andrade, Bruna Santos; Montanuci, Pietra Sally; Szumik, Claudia; Krolow, Tiago Kütter (Zootaxa, 2026)
The genus Clothoda, endemic to South America, comprises four valid species, three of which occur in the Amazon basin and one, C. tocantinensis, restricted to the Cerrado domain. This species was previously known from type locality in Taquaruçu, an area combing seasonal forests and cerrado vegetation but sharing climate similarities with Amazon. Of the four species, only C. nobilis and C. tocantinensis are recorded in Brazil. Because the taxonomy of female and immature Embioptera remains poorly= studied, we conducted fieldwork in Taquaruçu to collect colonies containing eggs, immatures and females. The collected specimens were reared under laboratory conditions. Here, we describe the female and immature stages of C. tocantinensis and provide illustrations, behavioral observations and development time data.